2010
DOI: 10.5194/acpd-10-4887-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How can aerosols affect the Asian summer monsoon? Assessment during three consecutive pre-monsoon seasons from CALIPSO satellite data

Abstract: Abstract. The impact of aerosols above and around the Tibetan Plateau on the Asian Summer Monsoon during pre-monsoon seasons March-April-May 2007, 2008, and 2009 is investigated by means of remote sensing and radiative transfer modelling. Four source regions are found to be responsible for the high aerosol loading around the Tibetan Plateau: the Taklamakan Desert, the Ganges Plains, the Indus Plains, and the Arabian Sea. CALIPSO lidar satellite data, providing vertically resolved images of aerosols, shows aero… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Daily average HR over IGP peaked at ~3 km to a value near 2 K d −1 , whereas the instantaneous SW HR is found to have a peak value of ∼ 6 K d −1 at around 3 km altitude. Based on CALIPSO observations, Kuhlmann and Quaas [] calculated HR during premonsoon seasons in three consecutive years (2006–2008) and found that HR peaks between 2 and 3 km over the Gangetic plains with a peak value of 0.35 K d −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Daily average HR over IGP peaked at ~3 km to a value near 2 K d −1 , whereas the instantaneous SW HR is found to have a peak value of ∼ 6 K d −1 at around 3 km altitude. Based on CALIPSO observations, Kuhlmann and Quaas [] calculated HR during premonsoon seasons in three consecutive years (2006–2008) and found that HR peaks between 2 and 3 km over the Gangetic plains with a peak value of 0.35 K d −1 .…”
Section: Resultsmentioning
confidence: 99%
“…They showed that aerosol loading over the IGP region is dominated by dust and is vertically extended to high altitude (~5 km) with enhanced heating in the middle troposphere (5–6 km). Kuhlmann and Quaas [] analyzed CALIPSO observations and calculated the HR profiles during the premonsoon seasons in three consecutive years (2006–2008) over the region 20°N to 50°N and 60°E to 120°E, covering a vast region including Tibetan Plateau, Taklamakan Desert, Ganges and Indus Plains, and Arabian Sea. All these studies either focused over only a part of IGP or used satellite data which has considerable uncertainty, and the Gangetic‐Himalayan (GH) region is not yet covered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, global climate models are limited by relatively coarse spatial resolution, which may preclude accurate representation of aerosol transport over the Tibetan Plateau. In a study using observed vertically resolved aerosol distributions over the Tibetan Plateau and surrounding regions, Kuhlmann and Quaas [] use observed surface albedo and a radiative transfer model to show that aerosols do not produce the large elevated heating needed to drive the Elevated Heat Pump. In the non‐monsoon season, wintertime pollution as observed in the Indian Ocean Experiment reduced the meridional temperature gradient in the global model study of Ramanathan et al .…”
Section: Black Carbon Interactions With Cloudsmentioning
confidence: 99%
“…It has been reported that only 25% contribution to the global aerosol emission comes from the anthropogenic sources, whereas maximum share (about 75%) comes from the natural dust [ Ginoux et al ., ]. This fact is supported by observational studies as well [ Gautam et al ., ; Kuhlmann and Quaas , ]. But, most of the studies (recent and previous) are centered on the summer monsoon connections with the anthropogenic aerosols.…”
Section: Introductionmentioning
confidence: 99%